Enhancing diradical character of chichibabin's hydrocarbon through fluoride substitution - Kundu, Gargi; Dash, Soumya Ranjan; Kumar, Ravi; Vanka, Kumar; Ghosh, Aryya; Sen, Sakya S. (ChemPlusChem, 2023)
In this work, 5-SIDipp [SIDipp=1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] (1) derived Chichibabin's hydrocarbon with an octafluorobiphenylene spacer (3) has been reported. The addition of two equivalents of 5-SIDipp with decafluorobiphenyl in presence of BF3 gives the double C-F bond activated imidazolium salt with two tetrafluoroborate anions, 2. Further reduction of 2 gives the fluorine substituted 5-SIDipp based Chichibabin's hydrocarbon, 3. Quantum chemical calculations suggested a singlet state of 3 with a singlet-triplet energy gap (?ES-T) of 3.7 kcal mol(-1), which is substantially lower with respect to the hydrogen substituted NHC-based Chichibabin's hydrocarbons (10.7 kcal mol(-1), B3LYP). As a result, the diradical character (y) of 3 (y=0.62) is also noticeably higher than the hydrogen substituted CHs (y=0.41-0.43). The ?ES-T was found to be higher in CASSCF (22.24 kcal mol(-1)) and CASPT2 (11.17 kcal mol(-1)) for 3 and the diradical character (d) is 44.6 %.
Keywords: C-F Bond Activation; Chichibabin & PRIME; DFT; N-Heterocyclic carbene; s Hydrocarbon